Academic Senate Minutes 2010-05-27 - Academic Senate:::::::::
Approval of Agenda. BS change in Geology – approved. Name change of LSEE to LEEE – approved. Linguistics move from Anthropology to English – approved. Curriculum Guide changes information item. President Report. Provost Report. Vice President for Administration and Finance Report. Associated Students Report. Vice President of SAEM Report. Chair-Elect Report. Ad-Hoc Diversity Committee Report. Revision to the WEPT Policy – Approved. Representation on Administrative Appointment Committees Policy Revision – Approved. Changes to S&F By-Laws – Approved. APC Report. 3-Unit GE Policy Revision – First Reading. Constitutional amendment – Emeritus Faculty Member of Senate - The manner in which this Emeritus representative is selected shall be established in the By-Laws – Approved. Proposal of Online Forum related to the tabled no confidence resolution – no action. Senators to the Executive Committee for 2010-2011 – S. Brannen and M. Purser. CFA Report. Changing of the Guard. Resolution Acclaiming and Commending Susan Moulton, Chair of the Faculty, 2009-2010 approved by acclimation.